KEMAMPUAN KOMUNIKASI DAN DISPOSISI MATEMATIS MAHASISWA PADA MATA KULIAH GEOMETRI - NOLA NARI (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2015)
This research was motivated by a fact that some of students of mathematics study program at STAIN Batusangkar have low ability in mathematics communication and mathematics disposition on Geometry subject. This is indicated by the students’ inability to answer the questions on mathematics communication. In order to solve this problem, the researcher designed a research on learning strategy using Problem-based in Geometry subject. This research applied experimental method using randomized control group only design. The population of this research was the third semester students registered in 2014/2015 academic year. They consisted of three classes. The data were taken from the final test of each sample. The research findings show that the two hypotheses were accepted. Therefore, students’ ability was better in mathematics communication by applying learning strategy using problem-based than conventional learning. In addition to this, students’ ability was better in mathematics disposition by using learning strategy using problem-based than conventional learning.Kata kunci: Kemampuan komunikasi, disposisi matematis, dan strategi pembelajaran berbasis masalah